The Weakness of the Strong Sex: Differences Between Men and Women Affected by Diabetic Foot Disease. (March 2023) - Iacopi, Elisabetta; Pieruzzi, Letizia; Riitano, Nicola; Abbruzzese, Lorenza; Goretti, Chiara; Piaggesi, Alberto
We aimed to analyze sex-related differences in clinical outcomes among patients with diabetic foot disease (DFD) managed in a third-level referral center. We retrospectively analyzed data of admissions performed in our department between 2011 and 2015 for DFD. We collected demographic and clinical data, procedures performed during the admission, and short- and long-term outcomes in terms of healing rate and healing time, major amputation, and mortality rates during the follow-up. We focused on differences between genders and tried to figure out if sex could be considered a predictive factor. We collected data from 1237 admission performed in 842 patients (615 men [73%] and 227 women [27%]; age: 68.6 ± 27.9 years; diabetes duration: 16.4 ± 13.4 years; body mass index: 28.2 ± 6.4 kg/m 2 ; hemoglobin A1c 7.9 ± 1.9%). Men showed a higher prevalence of comorbidities and previous ulcers or revascularization procedures. Men had a significantly higher healing rate compared with women (85.4% vs 63.2%, P < .001), but a longer healing time (124 ± 27 days vs 87 ± 14 days, P = .02). Major amputation did not differ between groups, while mortality rate was significantly higher in men (24.5% vs 16.1%, P = .02). In Cox's regression analysis, male sex was a positive predictive factor for healing and a negative one for time to heal and mortality. The difference in mortality was confirmed by a Kaplan-Meier analysis (log rank test: P = .03). DFD represents a severe disease and a strong marker of mortality affecting more severely on clinical outcomes and survival on men.